ANALISIS PROSES PEMBELAJARAN FISIKA BERBASIS PROBLEM BASED LEARNING - Apit Fathurohman; Hannah Marsanda Lutfi (Pendidikan Fisika UIN Alauddin Makassar, 2022)
This study aims to determine the process of applying physics learning based on problem based learning at SMA Negeri 1 Suak Tapeh. The method in this study is a descriptive method with a qualitative approach. Data were obtained from observations and interviews with physics subject teachers and documentation. In analyzing this research, data reduction, data presentation, and conclusion were drawn. The result of this research is the physics learning process still uses conventional learning models by way of lecturing to students but there is an approach that uses other learning models but not completely. learning with problem based learning models, the implementation of the independent curriculum has been implemented, but the PBL model has not been fully implemented due to the curriculum transfer process. PBL is in accordance with collaborative learning in solving existing problems in accordance with physics learning. The application of problem-based learning models in physics learning is only part of the teachers who apply it to achieve better learning such as physics learning which studies natural phenomena, as well as the surrounding environment so that it is feasible to be implemented in learning. process. learning. The problem-based learning process is based on the application of Pancasila profile learning by producing projects that start from solving problems related to the environment.